Elector crime - الشمري, منيف حواس (Journal of Legal Sciences, 2021)
Electoral crimes are both significant and sensitive ones، given that they touch the essence of the elections and the resulting political process. They are among the crimes that bear a special and interim nature، as they touch upon the very core of the political process and the resulting political system.Therefore، the bill has safeguarded them with several guarantees to reduce its occurrence and set a penalty for those who violate them.The electoral crimes occur within a limited time period during the electoral phase، be it in the preparatory stage، the election phase، or within the stage of counting، sorting and announcing the results، as these crimes are mostly committed by the candidate or voter or any other person.Thus، the electoral crime is of a special nature that concurrently affects the right of the voter and the candidate.Furthermore، the legislation did not agree on a specific name for this crime. Some of whom call it electoral crimes، and others calls it election crimes. The Iraqi draft law has imposed punitive provisions in the Council of Representatives Elections Law No. (9) for the year (2020).